A web interface for accessing scheduling methods in a distributed knowledge base - Varela, M.L.R. (2004)
With the increase of the Internet and virtual communities, interfaces for web applications and automated services are becoming an emergent necessity. In this paper we propose a web interface for enabling access to different manufacturing scheduling methods, which can be remotely available and accessible from a distributed knowledge base. Through this interface users can register and join together as a community and share their scheduling knowledge. Scheduling problems can occur in several different manufacturing environments and the web system searches in the distributed knowledge base for appropriate solving methods. Therefore, through this interface once suitable available methods, for a given problem, are identified it enables running one or more of them, made accessible by the system. Moreover, new methods can be continuously incorporated in the system's distributed repository, in a user-friendly way, feeding the knowledge base.